Raising Healthy Children: Age One - Anghela Z. Paredes; Karla P. Shelnutt (EDIS)
FCS8888, a 4-page illustrated fact sheet by Anghela Z. Paredes and Karla P. Shelnutt, provides general guidelines for parents of one-year old’s in nutrition, physical activity, and language and social development. Includes references. Published by the UF Department of Family Youth and Community Sciences, January 2010.